2007
DOI: 10.1074/jbc.m609727200
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear Export Signal of Splicing Factor Uap56p Interacts with Nuclear Pore-associated Protein Rae1p for mRNA Export in Schizosaccharomyces pombe

Abstract: Mammalian UAP56 or its homolog Sub2p in Saccharomyces cerevisiae are members of the ATP-dependent RNA helicase family and are required for splicing and nuclear export of mRNA. Previously we showed that in Schizosaccharomyces pombe Uap56p is critical for mRNA export. It links the mRNA adapter Mlo3p, a homolog of Yra1p in S. cerevisiae or Aly in mammals, to nuclear pore-associated mRNA export factor Rae1p. In this study we show that, in contrast to S. cerevisiae, Uap56p in S. pombe is not required for pre-mRNA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
(30 reference statements)
3
11
0
Order By: Relevance
“…Nucleocytoplasmic shuttling appears to be conserved from yeast to human UAP56, as it has been reported that Uap56p of Schizosaccharomyces pombe ( S.pombe) is also able to exit the nucleus [36]. The NES of Uap56p was mapped to its amino acids 250 to 350, a region that coincided with a domain required for binding of the nuclear pore-associated protein Rae1p.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Nucleocytoplasmic shuttling appears to be conserved from yeast to human UAP56, as it has been reported that Uap56p of Schizosaccharomyces pombe ( S.pombe) is also able to exit the nucleus [36]. The NES of Uap56p was mapped to its amino acids 250 to 350, a region that coincided with a domain required for binding of the nuclear pore-associated protein Rae1p.…”
Section: Resultsmentioning
confidence: 94%
“…The NES of Uap56p was mapped to its amino acids 250 to 350, a region that coincided with a domain required for binding of the nuclear pore-associated protein Rae1p. This interaction was critical for both, nucleocytoplasmic shuttling as well as UAP56p-mediated mRNA export [36]. Importantly, two single mutations, Q297R and F320A, within the UAP56p NES-region, partially abolished export, while a combination of both mutations led to a total loss of UAP56p shuttling.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Rad24p and Rae1p Are Enriched at DSB Sites in S. pombe Cells-We previously showed that Rae1p was not recruited to active genes (5,24). Also, it is not known whether Rad24 or any of its homologs recruit to genes.…”
Section: Dss1p Rhp51p and Mts2p Are Recruited To An Ho-endonucleasementioning
confidence: 99%
“…pombe Rae1p is essential for the nuclear export of mRNA and functions in cell cycle progression from G 2 to M (23,24). However, the role of Rae1p in the G 2 /M transition was shown to be independent of its role in mRNA export (25).…”
mentioning
confidence: 99%